Enrichment Young Local Entrepreneurs Through Merintis Indonesia Summit : In Collaboration With Ejsc (East Java Super Corridor) - Agustina Fitrianingrum; Roro Mega Cahyaning (ConCEPt - Conference on Community Engagement Project, 2021)
The increasing growth of collaborations that offer incubation and some entrepreneur programs for developing and facilitating the digital business, one of them is EJSC (East Java Super Corridor). EJSC (East Java Super Corridor) is is an institution under the auspices of the East Java Regional Coordinating Agency (Bakorwil) to bring the East Java Provincial Government (Pemprov) closer to the citizens. EJSC will serve community activities. The scope of this project is designing a new program which will be held for 3 months, 4 times a year. This program is called the Merintis Indonesia Summit, a creative hub to connect, collaborate & create digital business for local youth entrepreneurs into International level. The program includes digital business webinar talkshow, ideas summit day and mentoring classes to scale up and funding/investment stages. This study includes a qualitative case study to determine the topics of invention deployed by proto-entrepreneurs, and the activities that circumscribed idea development. The author used a convergent parallel mixed methods design to collect qualitative data on the process and products of Merintis Indonesia Summit. Started in October until December 2020, the project is done well and fit with project timeline, plan and budget. The project output is 10 new digital business that succed to be launched in 3 months and still going on for the next 3 batches in a year.